State Digital Sovereignty in the Regulation of Global Social Media Platforms - Adhe Ismail Ananda; Ayun Hapsari (Jurnal Hukum Siber dan Regulasi Teknologi, 2026)
The globalization of digital space and the dominance of global social media platforms have created new challenges for states in maintaining sovereignty in cyberspace. Communication activities, information distribution, and the management of citizens’ data now largely take place on cross-border platforms controlled by global corporations. This situation raises questions regarding the limits of state authority in regulating social media platforms and its implications for freedom of expression, data protection, and national interests. This study employs a normative juridical approach by examining Indonesian legislation, principles of international law, and the doctrine of digital sovereignty. The findings show that state digital sovereignty represents an adaptation of the classical concept of sovereignty, emphasizing the state’s authority to regulate digital activities that affect its citizens and the public interest. The regulation of global social media platforms has a dual implication: it strengthens the protection of national interests while at the same time potentially restricting freedom of expression if not implemented proportionally. In addition, the strengthening of digital sovereignty poses the risk of internet fragmentation if it is not accompanied by a harmonious approach aligned with the principles of global openness. Therefore, a model of digital sovereignty regulation is required that balances state authority, the protection of human rights, and the need for international cooperation in order to build a fair and sustainable digital governance framework.